Unfired ceramsite prepared by solidifying Bayer process red mud with solid waste material and preparation method of unfired ceramsite
By mixing the sintered red mud waste slag with a variety of industrial solid waste, and using composite excitants to stimulate gelling activity and form a dense protective film, high added value-free sintered ceratops are prepared, which solves the problem of low utilization rate of Bayer red mud in the existing technology, and achieves the resource utilization of solid waste and the performance of ceratops.
Patent Information
- Application Number
- CN202510100604.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the preparation of ceramic granules by mixing the Bayer method red mud active powder has a problem of low utilization, which leads to a large accumulation of red mud, occupying land, wasting resources, and endangering the ecological environment and human health.
The sintered red mud waste slag produced by aluminum smelting enterprises is mixed with a variety of industrial solid waste (such as granulated blast furnace slag powder, domestic waste incinerator slag, sintered red mud, desulfurized gypsum, etc.), and the gelling activity is stimulated by composite excitants, and a dense protective film is formed on the surface to prepare high added value-free sintered ceramic granules.
It has realized the resource utilization of solid waste, reduced the environmental pollution of industrial waste, saved energy, reduced carbon dioxide emissions, improved the strength and durability of ceramides, reduced production costs, and had good economic benefits.
Smart Images

Figure CN119874313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramsite products, in particular to unburned ceramsite for solidifying Bayer red mud with solid waste materials and a preparation method thereof. Background Art
[0002] Due to its low density, high cylinder pressure strength and high porosity, expanded clay has been widely used in many fields such as building materials, pipeline insulation, furnace insulation, cold insulation, heat insulation, sound insulation and sound absorption. It can also be used as soilless base bed material and water filtration material in agriculture and gardening.
[0003] Solid waste-based cementitious materials are usually made by mixing solid waste with some industrial solid waste and chemical additives, and are prepared after crushing, grinding and mixing. They are inorganic cementitious materials with excellent properties such as corrosion resistance, low shrinkage and low hydration heat. The use of this material will help reduce the environmental burden of industrial solid waste and will also reduce the high energy consumption and carbon emissions of the traditional cement industry.
[0004] Bayer red mud is a residue produced during the refining of alumina. It has complex composition, huge emissions, strong alkalinity, large specific surface area, and various components wrapped and embedded in each other. It is difficult to dispose of it on a large scale by relying on treatment methods to improve its activity. Moreover, the existing building materials made from red mud have defects such as high cost, poor efficiency, and low technical maturity.
[0005] The existing patent documents on unfired ceramsite made of solid waste-based cementitious materials mainly include: (1) an industrial, agricultural and urban solid waste-based ceramsite and its preparation method and application, publication number CN114804910B; (2) a method for preparing unfired ceramsite using solid waste-based sulphoaluminate cementitious materials, publication number CN109020418B; (3) a method for preparing ultra-light ceramsite using coal gangue and solid waste, publication number CN117209253B. The patent documents on unfired expanded clay prepared by activating red mud mainly include: (1) a method for preparing high-strength supported semi-vitrified expanded clay using low-silica red mud raw materials, publication number CN111196713B; (2) a multi-level pore structure red mud-based unfired expanded clay water purification filler and a preparation method thereof, publication number CN112777973B; (3) a red mud-based expanded clay concrete and a preparation method and application thereof, publication number CN111302746B; (4) a high-strength expanded clay based on industrial solid waste and a preparation method thereof, publication number CN116675454A.
[0006] Among the above-mentioned existing patents for unfired ceramsite, some use solid waste-based cementitious materials to directly prepare ceramsite, and some use Bayer red mud active powder to mix and prepare ceramsite. The use of solid waste cementitious materials to prepare ceramsite illustrates the feasibility of the technology, but there is a problem of low utilization rate by improving the activity of Bayer red mud. In view of the current large-scale accumulation of Bayer red mud, it not only occupies land and wastes resources, but also has seriously endangered the ecological environment safety and people's health. Therefore, the present invention uses the sintering red mud waste residue produced by aluminum smelting enterprises to prepare Bayer red mud with very low solidification activity of solid waste cementitious materials, prepare ceramsite products with high added value, and realize the resource utilization of solid waste. Summary of the invention
[0007] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, a method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials is provided.
[0008] The technical solution adopted by the present invention is: a kind of unburned ceramsite for solidifying Bayer red mud with solid waste materials, which comprises 50%-80% of solid waste-based cementitious material and 20-50% of Bayer red mud in terms of mass percentage;
[0009] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 40-60% of S95 granulated blast furnace slag powder, 15-30% of domestic waste incineration slag, 10-20% of sintering red mud, 10-20% of desulfurized gypsum, 0.8%-1.4% of composite activator, and 0.01%-0.05% of triethanolamine; the raw materials of the above-mentioned solid waste-based cementitious materials are all the mass after drying.
[0010] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1: (8-22): (2-10). The composite activator provides OH- ions to react with the glass in the solid waste, destroying the aluminum-oxygen tetrahedron and silicon-oxygen tetrahedron structures, breaking the Si-O-Si, Si-O-Al and Al-O-Al bonds in the aluminosilicate glass, exposing groups containing active silanol groups, thereby stimulating the gelling activity of the solid waste. Furthermore, potassium alum can react with AlO in an alkaline environment. 2- and Ca 2+ The reaction generates ettringite mineral phase, which improves the mechanical properties of the cementitious material.
[0011] Furthermore, the triethanolamine of the present invention chemically reacts with metal on the surface of the solid waste-based gelling material to form a dense protective film;
[0012] By adopting the above technical solution, a dense protective film is generated to prevent adhesion between particles, reduce friction between particles, and improve grinding efficiency.
[0013] Furthermore, the solid waste-based gelling material of the present invention is obtained by drying the raw materials, weighing and mixing them according to a mass ratio, and grinding them.
[0014] Furthermore, the particle size of the solid waste-based cementitious material after grinding is D10≤1.2 microns, D50≤5.6 microns, and D90≤40 microns.
[0015] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials comprises the following steps:
[0016] A. 80% by weight of solid waste-based cementitious materials and Bayer red mud are premixed to obtain a dry powder mixture;
[0017] B. Add industrial water to the dry powder mixture, and then mix evenly to obtain a granulated mixture;
[0018] C. Pour the granulation mixture into the granulator, turn on the power, and slowly sprinkle the remaining 20% by mass of the solid waste-based gelling material into the granulator during the granulation process to finally obtain raw ceramsite;
[0019] D. Take out the expanded clay produced in the granulator and place it in the room for natural curing for 3-7 days to obtain the unburned expanded clay of Bayer red mud solidified by solid waste-based cementitious material.
[0020] Furthermore, the fineness of the Bayer process red mud described in step A of the present invention is greater than 200 meshes.
[0021] Furthermore, in step B of the present invention, the amount of industrial water added is 0.14-0.21 of the mass of the dry powder mixture.
[0022] Furthermore, the particle size of the raw ceramsite in step C of the present invention is 0-5 mm.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. The present invention realizes the resource utilization of solid waste and reduces the pollution of industrial waste to the environment by converting various industrial solid wastes (such as granulated blast furnace slag powder, domestic waste incineration slag, sintering red mud, desulfurized gypsum, etc.) into cementitious materials; the production process of unfired ceramsite does not require high-temperature sintering, thereby saving energy and reducing the emission of carbon dioxide and other greenhouse gases, meeting the requirements of low-carbon environmental protection.
[0025] 2. The use of composite activators significantly improves the mechanical properties of cementitious materials, making the final product have better strength and durability.
[0026] 3. The preparation method of the present invention is simple, easy to operate, and easy to industrialize, which is conducive to promotion and application. Furthermore, the use of low-cost solid waste as raw materials reduces production costs, and the prepared unfired ceramsite has a high market value and good economic benefits.
[0027] 4. The natural curing method is adopted, without the need for additional heating or accelerated curing process, which further reduces energy consumption and costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a microscopic image of the solid waste-based cementitious material in Example 1.
[0029] Figure 2 This is a test chart for particle size distribution analysis of solid waste-based cementitious materials in Example 1.
[0030] Figure 3 This is the appearance of the unfired ceramsite prepared in Example 1.
[0031] Figure 4 This is the appearance of the unfired ceramsite prepared in Example 2.
[0032] Figure 5 This is the appearance of the unfired ceramsite prepared in Example 3.
[0033] Figure 6 This is the appearance of the unfired ceramsite prepared in Example 4.
[0034] Figure 7 This is the appearance of the unfired ceramsite prepared in Example 5. DETAILED DESCRIPTION
[0035] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0036] Example 1
[0037] A non-fired ceramsite for solidifying Bayer red mud with solid waste materials, comprising 70% of solid waste-based cementitious material and 30% of Bayer red mud by mass percentage;
[0038] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 50% of S95 granulated blast furnace slag powder, 20% of domestic waste incineration slag, 20% of sintering red mud, 10% of desulfurized gypsum, 0.8% of composite activator, and 0.02% of triethanolamine;
[0039] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1:10:5. The composite activator provides OH- ions to react with the glass in the solid waste, destroying the aluminum-oxygen tetrahedron and silicon-oxygen tetrahedron structures, breaking the Si-O-Si, Si-O-Al and Al-O-Al bonds in the aluminosilicate glass, exposing groups containing active silanol groups, thereby stimulating the gelling activity of the solid waste. Furthermore, potassium alum can react with AlO in an alkaline environment. 2- and Ca 2+ The reaction generates ettringite mineral phase, which improves the mechanical properties of the cementitious material.
[0040] The triethanolamine reacts chemically with the metal on the surface of the solid waste-based gelling material to form a dense protective film. The solid waste-based gelling material is obtained by drying the raw materials, weighing and mixing them according to a mass ratio, and grinding them.
[0041] The particle size of the solid waste-based cementitious material after grinding is D10 = 0.748 microns, D50 = 3.611 microns, and D90 = 34.47 microns (its microscopic appearance is shown in the figure Figure 1 As shown in the figure, the particle size distribution analysis test diagram is as follows Figure 2 shown).
[0042] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials comprises the following steps:
[0043] A. 80% by weight of solid waste-based cementitious materials and Bayer red mud are premixed to obtain a dry powder mixture;
[0044] B. Add industrial water to the dry powder mixture, and then mix evenly to obtain a granulated mixture;
[0045] C. Pour the granulation mixture into the granulator, turn on the power, and slowly sprinkle the remaining 20% by mass of the solid waste-based gelling material into the granulator during the granulation process to finally obtain raw ceramsite;
[0046] D. Take out the ceramsite produced in the granulator and place it in the room for natural curing for 5 days to obtain the unburned ceramsite (appearance as Figure 3 shown).
[0047] Wherein, the fineness of the Bayer red mud in step A is greater than 200 mesh. In step B, the amount of industrial water added is 0.15 of the mass of the dry powder mixture. In step C, the particle size of the raw ceramsite is 0-5 mm.
[0048] Example 2
[0049] A kind of unburned ceramsite (appearance as Figure 4As shown), the difference from Example 1 is that: the components by mass percentage include 80% of solid waste-based cementitious materials and 20% of Bayer red mud;
[0050] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 40% of S95 granulated blast furnace slag powder, 28% of domestic waste incineration slag, 16% of sintering red mud, 16% of desulfurized gypsum, 1% of composite activator, and 0.04% of triethanolamine;
[0051] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1:9:4.5.
[0052] The particle sizes of the solid waste-based cementitious material after grinding are D10=0.817 microns, D50=4.6 microns, and D90≤28.4 microns.
[0053] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials, which differs from Example 1 in that: the amount of industrial water added in step B is 0.18 of the mass of the dry powder mixture; in step D, the ceramsite prepared in the granulator is taken out and placed indoors for natural curing for 7 days.
[0054] Example 3
[0055] A kind of unburned ceramsite (appearance as Figure 5 As shown), the difference from Example 1 is that: the components by mass percentage include 65% of solid waste-based cementitious material and 35% of Bayer red mud;
[0056] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 45% of S95 granulated blast furnace slag powder, 24% of domestic waste incineration slag, 18% of sintering red mud, 13% of desulfurized gypsum, 0.6% of composite activator, and 0.01% of triethanolamine;
[0057] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1:10:6.
[0058] The particle sizes of the solid waste-based cementitious material after grinding are D10=0.764 microns, D50=3.9 microns, and D90≤34.7 microns.
[0059] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials, which differs from Example 1 in that: the amount of industrial water added in step B is 0.18 of the mass of the dry powder mixture; in step D, the ceramsite prepared in the granulator is taken out and placed indoors for natural curing for 6 days.
[0060] Example 4
[0061] A kind of unburned ceramsite (appearance as Figure 6 As shown), the difference from Example 1 is that: the components by mass percentage include 60% of solid waste-based cementitious material and 40% of Bayer red mud;
[0062] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 55% of S95 granulated blast furnace slag powder, 20% of domestic waste incineration slag, 14% of sintering red mud, 11% of desulfurized gypsum, 1.2% of composite activator, and 0.03% of triethanolamine;
[0063] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1:11:6.5.
[0064] The particle sizes of the solid waste-based cementitious material after grinding are D10=0.698 microns, D50=3.69 microns, and D90≤37.4 microns.
[0065] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials, which differs from Example 1 in that: the amount of industrial water added in step B is 0.17 of the mass of the dry powder mixture; in step D, the ceramsite prepared in the granulator is taken out and placed indoors for natural curing for 7 days.
[0066] Example 5
[0067] A kind of unburned ceramsite (appearance as Figure 7 As shown), the difference from Example 1 is that: the components by mass percentage include 50% solid waste-based cementitious material and 50% Bayer red mud;
[0068] The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 60% of S95 granulated blast furnace slag powder, 15% of domestic waste incineration slag, 15% of sintering red mud, 10% of desulfurized gypsum, 0.8% of composite activator, and 0.06% of triethanolamine;
[0069] The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1:12:8.
[0070] The particle sizes of the solid waste-based cementitious material after grinding are D10=0.824 microns, D50=3.8 microns, and D90≤36.7 microns.
[0071] A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials, which differs from Example 1 in that: the amount of industrial water added in step B is 0.16 of the mass of the dry powder mixture; in step D, the ceramsite prepared in the granulator is taken out and placed indoors for natural curing for 7 days.
[0072] The unburned ceramsite of the above embodiment is tested according to the specifications of GB / T 17431.1-2010 "Light aggregate and its test methods Part 1: Light aggregate" and GB / T17431.2-2010 "Light aggregate and its test methods Part 2: Light aggregate test method", and the specific test results are shown in Table 1.
[0073] Table 1 Test results
[0074] project 1h water absorption rate (%) Porosity (%) Apparent density (g / cm3) Cylinder compressive strength (MPa) Example 1 10.6 0.12 1.41 7.78 Example 2 12.9 0.10 1.47 8.65 Example 3 11.7 0.08 1.36 6.55 Example 4 10.5 0.14 1.38 6.42 Example 5 11.8 0.05 1.35 5.84
Claims
1. A kind of unburned ceramsite for solidifying Bayer red mud with solid waste material, characterized by: The components by mass percentage include 50%-80% solid waste-based cementitious materials and 20-50% Bayer red mud; The solid waste-based cementitious material is composed of the following raw material components in percentage by mass: 40-60% of S95 granulated blast furnace slag powder, 15-30% of domestic waste incineration slag, 10-20% of sintering red mud, 10-20% of desulfurized gypsum, 0.8%-1.4% of composite activator, and 0.01%-0.05% of triethanolamine; The composite activator comprises sodium carbonate, quicklime and potassium alum mixed in a mass ratio of 1: (8-22): (2-10). The composite activator provides OH- ions to react with the glass in the solid waste, destroying the aluminum-oxygen tetrahedron and silicon-oxygen tetrahedron structures, breaking the Si-O-Si, Si-O-Al and Al-O-Al bonds in the aluminosilicate glass, exposing groups containing active silanol groups, thereby stimulating the gelling activity of the solid waste. Furthermore, potassium alum can react with AlO in an alkaline environment. 2- and Ca 2+ The reaction generates ettringite mineral phase, which improves the mechanical properties of the cementitious material.
2. The unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 1, characterized in that: The triethanolamine chemically reacts with the metal on the surface of the solid waste-based gelling material to form a dense protective film.
3. The unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 1, characterized in that: The solid waste-based gelling material is obtained by drying various raw materials, weighing and mixing them according to mass proportions, and grinding them.
4. The unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 3, characterized in that: The particle size of the solid waste-based gelling material after grinding is D10≤1.2 microns, D50≤5.6 microns, and D90≤40 microns.
5. A method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials, characterized in that: The following steps are involved: A. 80% by weight of solid waste-based cementitious materials and Bayer red mud are premixed to obtain a dry powder mixture; B. Add industrial water to the dry powder mixture, and then mix evenly to obtain a granulated mixture; C. Pour the granulation mixture into the granulator, turn on the power, and slowly sprinkle the remaining 20% by mass of the solid waste-based gelling material into the granulator during the granulation process to finally obtain raw ceramsite; D. Take out the expanded clay produced in the granulator and place it in the room for natural curing for 3-7 days to obtain the unburned expanded clay of Bayer red mud solidified by solid waste-based cementitious material.
6. The method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 5, characterized in that: The fineness of the Bayer process red mud described in step A is greater than 200 meshes.
7. The method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 5, characterized in that: In step B, the amount of industrial water added is 0.14-0.21 of the mass of the dry powder mixture.
8. The method for preparing unburned ceramsite for solidifying Bayer red mud with solid waste materials as claimed in claim 5, characterized in that: The particle size of the raw ceramsite in step C is 0-5 mm.
Citation Information
Patent Citations
A method for preparing non-fired ceramsite from solid waste-based sulfoaluminate cementitious materials.
CN109020418B
A method for preparing high-strength supported semi-vitrified ceramic particles using low-silica red mud as raw material
CN111196713B
A Red Mud-Based Ceramsite Concrete, Its Preparation Method and Application
CN111302746B
A multi-level porous structure red mud-based non-fired ceramsite water purification filler and its preparation method
CN112777973B
A type of ceramsite based on solid waste from industrial, agricultural, and urban areas, its preparation method, and its application.
CN114804910B